Pricing and introductory scarcity strategies based on consumers' response. (19th December 2019) - Chen, Shaohua; Jia, Junxiu
Abstract: In industries such as electronics, automobiles, and luxury goods, we have observed numerous cases of intentional undersupply when a new product is introduced. Previous research has shown that introductory scarcity has a positive effect on consumers' willingness to pay, but this effect has yet to be quantified. This paper investigates how scarcity strategies affect product pricing and a firm's profits. We consider two types of scarcity strategies, a real and a fake scarcity strategy, and propose a two‐period model in both markdown and markup scenarios. We find that an introductory scarcity strategy is profitable in a markup scenario only if the discount factor is greater than a critical value and payoffs are compartmentalized. Moreover, an introductory scarcity strategy could result in profits in a markdown scenario if consumers are sensitive to scarcity. However, a scarcity strategy is always detrimental to a firm with low‐quality products in both scenarios. If there are uninformed consumers in the market, a fake scarcity strategy is beneficial for firms in the short term but not in the long term.